The labor Welfare Conditions in a Company in the Hospitality Industry. Case study. Medellin, Colombia. - Jiménez-González, Gloria María; Rivera-Ladino, Ana María; Gaibao-Pérez, María Carolina (Prospectiva. Revista de Trabajo Social e Intervención Social, 2019)
The labor welfare conditions of the workers of a company in the hospitality industry of the city of Medellin are addressed in order to know the workers’ living conditions, which in some way can affect their productivity, put at risk their psychosocial conditions and the success of the business strategy. From the profession of social work in conjunction with the area of ​​human management, the workers’ quality of life and the perception that they have of their company are investigated with an emphasis on quantitative analysis and the use of case studies as strategy. Despite the results, which highlights that the majority of workers earn between one or two minimum wages, workers manifest satisfaction and sense of belonging to the company, where the salary is not their main motivation, on the contrary, good treatment, benefits, stability, and support in times of crisis, become the main attractions to be part of the organization.